Semantic model-driven development of web service architectures. (16th July 2008) - Pahl, Claus
Building service-based architectures has become a major area of interest since the advent of web services. Modelling these architectures is a central activity. Model-driven development is a recent approach to developing software systems based on the idea of making models the central artefacts for design representation, analysis and code generation. We propose an ontology-based engineering methodology for semantic model-driven composition and transformation of web service architectures. Ontology technology as a logic-based knowledge representation and reasoning framework can provide answers to the needs of sharable and reusable semantic models and descriptions needed for service engineering. Based on modelling, composition and code generation techniques for service architectures, our approach provides a methodological framework for ontology-based semantic service architecture.